2018
DOI: 10.1371/journal.pone.0199013
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced transformation of incidentally learned knowledge into explicit memory by dopaminergic modulation

Abstract: During incidental learning statistical regularities are extracted from the environment without the intention to learn. Acquired implicit memory of these regularities can affect behavior in the absence of awareness. However, conscious insight in the underlying regularities can also develop during learning. Such emergence of explicit memory is an important learning mechanism that is assumed to involve prediction errors in the striatum and to be dopamine-dependent. Here we directly tested this hypothesis by manip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 67 publications
0
8
0
Order By: Relevance
“…We had to use a between-group design rather than a more powerful within-group crossover design because of the limited stimulus set and possible interference effects between the picture-word pairs. Additionally, also another task measured in this sample (Clos et al, 2018) was incompatible with a within-group design. Fifty-three of these participants (13 males, mean age 24 Ϯ 2.9 years; 27 haloperidol and 26 placebo) took part in the cued association recall paradigm.…”
Section: Participantsmentioning
confidence: 95%
See 2 more Smart Citations
“…We had to use a between-group design rather than a more powerful within-group crossover design because of the limited stimulus set and possible interference effects between the picture-word pairs. Additionally, also another task measured in this sample (Clos et al, 2018) was incompatible with a within-group design. Fifty-three of these participants (13 males, mean age 24 Ϯ 2.9 years; 27 haloperidol and 26 placebo) took part in the cued association recall paradigm.…”
Section: Participantsmentioning
confidence: 95%
“…We used a double-blind, placebo-controlled between-group design with 54 participants in total as part of a larger study (Clos et al, 2018(Clos et al, , 2019. We had to use a between-group design rather than a more powerful within-group crossover design because of the limited stimulus set and possible interference effects between the picture-word pairs.…”
Section: Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, encoding and consolidation of memories require the stimulation of dopamine receptors as part of a hippocampal-striatal-prefrontal loop that orchestrates the formation of new memories [2,3]. Dopaminergic effects on working memory (WM) are well established in animals and humans [4], but dopamine has also been reported to affect other domains of memory (e.g., [5,6]). For episodic memory, while several pharmacological studies reported dopaminergic effects on encoding or consolidation [7][8][9][10], effects on retrieval performance were often absent or inconclusive [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…A version of the Serial Reaction Time Task (SRTT) [27,28], an implicit motor task, modified from Clos and Sommer was used in this study [29]. Participants placed the fingers of their left (non-dominant) hand on a custom-made button box.…”
Section: Motor Task Paradigmmentioning
confidence: 99%